2018
DOI: 10.1590/1806-9282.64.08.745
|View full text |Cite
|
Sign up to set email alerts
|

Anthracycline-associated cardiotoxicity in adults: systematic review on the cardioprotective role of beta-blockers

Abstract: SUMMARY OBJECTIVES This study aimed at assessing the role of beta-blockers on preventing anthracycline-induced cardiotoxicity in adults. METHODS A systematic review was performed on electronic databases, including relevant studies that analysed beta-blockers as cardioprotective agents before the use of anthracyclines by adult oncologic patients. RESULTS After application of eligibility and selection criteria, eight articles were considered as high quality, complying with the proposed theme; all eight cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…DOX treatment significantly increased systolic BP of the animals compared to CON (157. 69 , p = 0.0037/p = 0.0027 (ACEI vs. CON), p = 0.0012/p = 0.0012 (ACEI vs. D-CON), p = 0.0083/p = 0.0014 (ACEI vs. BB), p = 0.0015/p = 0.0421 (ACEI vs. AA)] ( Fig. 2d, e , p = 0.001 (BB vs. CON), p = 0.0026 (BB vs. D-CON), p = 0.011 (BB vs. ACEI), p = 0.0055 (BB vs. AA)] (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOX treatment significantly increased systolic BP of the animals compared to CON (157. 69 , p = 0.0037/p = 0.0027 (ACEI vs. CON), p = 0.0012/p = 0.0012 (ACEI vs. D-CON), p = 0.0083/p = 0.0014 (ACEI vs. BB), p = 0.0015/p = 0.0421 (ACEI vs. AA)] ( Fig. 2d, e , p = 0.001 (BB vs. CON), p = 0.0026 (BB vs. D-CON), p = 0.011 (BB vs. ACEI), p = 0.0055 (BB vs. AA)] (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, no significant haemodynamic consequence of the eplerenone treatment could be seen in the animals at the applied dose (6.25 mg/kg). Previously, several smaller clinical trials [31-34, 57, 58, 66] and some meta-analyses [67][68][69][70] have investigated the prophylactic effects of BBs and ACEIs applied alone or in combination to prevent AC cardiotoxicity, however, their results were not always consistent. Although some study groups demonstrated the protective effects of the applied agent on the LV EF [31,33,34,66], others could not confirm the superiority of the study drug compared to placebo [32,57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Charak et al (Charak et al, 2018) also suggested that BBs were associated with better specific cancer survival. Furthermore, the results of a systematic review of eight high-quality studies (Barbosa et al, 2018) indicated that BBs had potential protective effects on the heart. Additionally, for early-stage cancer treated with surgery, BBs could prolong the survival period (Choi et al, 2014).…”
Section: Anti-hypertensive Drugs Have the Potential To Become Adjuvanmentioning
confidence: 99%
“…164 In different studies it has shown improvement in GLS more than in LVEF; in others, lower release of TnI and better diastolic function. 165,166 Nevibolol 167 and bisoprolol have some benefit; 165 metoprolol has a neutral effect 162 on results and propranolol has a cardiotoxic role. 165,166 • Statins.…”
Section: Addition Of Cardioprotective Drugsmentioning
confidence: 99%
“…165,166 Nevibolol 167 and bisoprolol have some benefit; 165 metoprolol has a neutral effect 162 on results and propranolol has a cardiotoxic role. 165,166 • Statins. There is evidence of its favorable effect on the prognosis with reduction in the BC recurrence at 5 years (0.67 for users vs non-users 95% CI, 0.39 to 1.13); 168 as well as in the preservation of ventricular function.…”
Section: Addition Of Cardioprotective Drugsmentioning
confidence: 99%